Factors affecting mother's planning in exclusive breastfeeding - Puji Astutik, Linda; Migang, Yena Wineini; Kusnaningsih, Aida (Institute of Computer Science (IOCS), 2024)
Exclusive breastfeeding, which means the baby is only given breast milk without any other food or drink for the first six months, contains all the nutrients the baby needs and immune substances that help boost their immune system. This study examines mothers' plans for exclusive breastfeeding and the factors that influence them. This study uses a retrospective cohort design. The research instrument used secondary data. Analysis use Chi Square test. It is known that primigravida and multigravida mothers tend to have plans for exclusive breastfeeding after being provided with 7 days of support. From the statistical test results, a p-value of 0.157 was obtained, concluding that gravida does not have an influence on the mother's plan for exclusive breastfeeding. Mothers without experience and those with experience in exclusive breastfeeding tend to have plans for exclusive breastfeeding after 7 days of support. From the statistical test results, a p-value of 0.570 was obtained, concluding that maternal experience does not influence the mother's plan for exclusive breastfeeding. Mothers with both negative and positive attitudes tend to have plans for exclusive breastfeeding. From the statistical test results, a p-value of 0.031 was obtained, concluding that the mother's attitude has an influence on the mother's plan for exclusive breastfeeding with an RR of 6.333. It is concluded that gravida, maternal experience does not have an influence on the mother's plan for exclusive breastfeeding, whereas the mother's attitude does have an influence on the mother's plan for exclusive breastfeeding.